Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT Bank Mndiri Tbk Kantor Cabang Pembantu Semarang Pandanaran - Ilma Tansa Shabrina; Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to examine and analyze the influence of leadership style, work motivation and job satisfaction on employee performance at PT Bank Mandiri Tbk Semarang Pandanaran Sub-Branch Office. The population in this study were all employees of PT Bank Mandiri Tbk Semarang Pandanaran Sub-Branch Office, totaling 58 employees. The sample in this research consisted of 58 employees. The sampling technique uses saturated sampling. This research data analysis tool uses multiple linear regression. The research results show that leadership style has a positive effect on employee performance. Work motivation has a positive effect on employee performance. Meanwhile, job satisfaction has no effect on the performance of employees of PT Bank Mandiri Tbk Semarang Pandanaran Sub-Branch Office.